2020
DOI: 10.1016/j.nicl.2020.102383
|View full text |Cite
|
Sign up to set email alerts
|

A TMS study of preparatory suppression in binge drinkers

Abstract: Highlights Normally, action preparation involves a global suppression of motor activity. Such preparatory suppression is deficient in alcohol-dependent patients. Binge drinking may represent a first step toward alcohol-use disorder. Here, we tested whether binge drinkers also display altered preparatory suppression. Our results indicate abnormally high motor preparatory activity in binge drinkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 115 publications
(174 reference statements)
3
35
0
Order By: Relevance
“…By contrast, because a higher excitatory drive was observed both in HDs and SAUDs, a greater tendency to act might represent a common feature of hazardous drinking. Interestingly, young binge-drinkers, who are also characterized by unhealthy drinking habits ( Lannoy et al, 2019 ), present a pattern of MEP changes remarkably similar to the one reported in HDs ( Grandjean and Duque, 2020 ). As such, they have been found to show a drastically weaker MEP suppression when probed in selected effectors, despite a normal suppression in task-irrelevant muscles ( Grandjean and Duque, 2020 ).…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…By contrast, because a higher excitatory drive was observed both in HDs and SAUDs, a greater tendency to act might represent a common feature of hazardous drinking. Interestingly, young binge-drinkers, who are also characterized by unhealthy drinking habits ( Lannoy et al, 2019 ), present a pattern of MEP changes remarkably similar to the one reported in HDs ( Grandjean and Duque, 2020 ). As such, they have been found to show a drastically weaker MEP suppression when probed in selected effectors, despite a normal suppression in task-irrelevant muscles ( Grandjean and Duque, 2020 ).…”
Section: Discussionmentioning
confidence: 54%
“…Hence, while the lack of MEP suppression in SAUDs was initially interpreted as reflecting a lack of inhibitory influences, an alternative explanation might be that the tendency to act was abnormally high in these subjects, causing an excessive excitatory drive in potential responders that was captured in our MEP measures ( Nardone et al, 2019 ). This hypothesis is supported by the recent observation that binge drinkers exhibit similar MEP suppression as healthy controls when probed in task-irrelevant muscles; the abnormality there only involved a weaker MEP suppression in the selected effector, which may thus reflect an abnormally strong tendency to act rather than deficient inhibition ( Grandjean and Duque, 2020 ).…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…Importantly, MEPs in these three muscles were obtained by stimulating a single spot. This hotspot was found for each M1 at the beginning of every single session in each subject; it corresponded to the hotspot of the ADM 107 , which usually provides the most consistent MEPs when these three muscles are considered together (see Figure S1.A). Further, eliciting concurrent MEPs in both hands allowed us to capture excitability changes on the two sides of the motor system at once (in each trial), thus concerning finger representations that are both on the side of the chosen index and on the side of the unchosen finger (e.g., right and left MEPs, respectively, preceding a right index finger choice).…”
Section: Transcranial Magnetic Stimulation (Tms) Over Finger Representationsmentioning
confidence: 81%